Role of Pyruvate Metabolism in the Growth of Streptococcus faecalis in the Presence of Propionate - Kamihara, Teijiro (1969)
The growth of Streptococcus faecalis is inhibited by propionate, and the inhibition is reversed by lipoic acid or acetate. A study of the role of pyruvate oxidation in S. faecalis showed that propionate inhibited the lipoic acid-dependent aerobic oxidation of pyruvate in resting cells. Pyruvate dehydrogenation with neotetrazolium as a hydrogen acceptor in cell-free extracts also required lipoic acid and was markedly inhibited by propionyl phosphate as well as sodium propionate. Some lipid substances, such as palmitate, oleate, behenate, and lecithin, had a lipoic acid-replacing effect on growth of the organism. Biotin or bicarbonate promoted the lipoic acid-dependent growth. Acetate-2-(14)C added to the medium was mainly incorporated into the lipid fraction of the cells. Evolution of (14)CO(2) from pyruvate-2-(14)C was not observed in resting cells of the organism, even under aerobic conditions. From the above findings, it is concluded that lipid synthesis through pyruvate oxidation plays a very important role in bacterial growth in medium containing propionate.